Cemetery Pilgrimage Tradition of Mahmud Custom Village to establish Social Motivation - Faturochman, Rizky; Nurbayani, Siti; Iqbal, Muhamad (Universitas Pendidikan Indonesia, 2018)
This study was started by the curiosity of the writer towards pilgrimage tradition and social motivation of pilgrimage who conduct cemetery pilgrimage in Mahmud Village. cemetery pilgrimage tradition is defined as an individual or a group movement that visit holy places. This site is considered as a sacred or holy, due to an exceptional event that was occurred in that place or there several sacred things that are placed there. This condition is related with a historical or legendary event. Cemetery Pilgrimage Tradition mostly are conducted by many people, for example in Mahmud Village, Bandung. The aims of this study were to recognize the background from the pilgrims, to recognize social motivation of the pilgrims before and after they conducted cemetery pilgrimage. The method used in this study is a descriptive case study by using qualitative approach. The data is gathered from natural setting as a direct source. Based on the analysis towards those data and fact. Including:Â self and group motivation, willingness to recognize cemetery site in mahmud village, willingness to feel calm after conducting cemetery pilgrimage, seeking for blessing, and expecting to fulfill his or her needs immediately by Allah SWT.